Interplay between trauma and Pseudomonas entomophila infection in flies: a central role of the JNK pathway and of CrebA. Issue 1 (December 2017) - Ragheb, Ramy; Chuyen, Alexandre; Torres, Magali; Defaye, Arnaud; Seyres, Denis; Kremmer, Laurent; Fernandez-Nunez, Nicolas; Tricoire, Hervé; Rihet, Pascal; Nguyen, Catherine; Röder, Laurence; Perrin, Laurent
Abstract In mammals, both sterile wounding and infection induce inflammation and activate the innate immune system, and the combination of both challenges may lead to severe health defects, revealing the importance of the balance between the intensity and resolution of the inflammatory response for the organism's fitness. Underlying mechanisms remain however elusive. Using Drosophila, we show that, upon infection with the entomopathogenic bacteriumPseudomonas entomophila (Pe), a sterile wounding induces a reduced resistance and increased host mortality. To identify the molecular mechanisms underlying the susceptibility of wounded flies to bacterial infection, we analyzed the very first steps of the process by comparing the transcriptome landscape of infected (simple hit flies, SH), wounded and infected (double hit flies, DH) and wounded (control) flies. We observed that overexpressed genes in DH flies compared to SH ones are significantly enriched in genes related to stress, including members of the JNK pathway. We demonstrated that the JNK pathway plays a central role in the DH phenotype by manipulating the Jra/dJun activity. Moreover, the CrebA/Creb3-like transcription factor (TF) and its targets were up-regulated in SH flies and we show that CrebA is required for mounting an appropriate immune response. Drosophila thus appears as a relevant model to investigate interactions between trauma and infection and allows to unravel key pathways involved.